Secondary education in transition in Nigeria: The question of quality: Secondary education in transition in Nigeria: The question of quality (Journal of Educational Management, 2000)
The paper traced the history of the development of secondary education in Nigeria since its inception in J859. The paper noted the emphasis on traditional art and science subjects in the past and the innovations that have been brought into the secondary school curricula by the National Policy 011 Education published in 1977, but revised in J981 and J998. The problems of implementing the curricula were briefly mentioned. The paper finally highlighted steps that could be taken to improve the quality of secondary education, such as provision of physical and material resources, adequate financing of education, teacher training and development, improvement of the conditions of service for teachers and supervision of instruction, among others.